Negotiating positionality amid postcolonial knowledge relations: insights from Nordic-based Sub-Saharan African academics - Ezechukwu Gabriel U. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This article is concerned with the issue of positionality in the context of transnational academic career. Focusing on the views and experiences of Nordic-based Sub-Saharan African academics, the paper adopts a transcolonial perspective to examine the role of coloniality in framing the academics' positions within Nordic and African higher education spaces. In doing so, this article contributes to the understanding of how some well-established inequalities are produced and reproduced within a seemingly innocuous policy sphere such as internationalization. By focusing on two different postcolonial contexts, it also serves as a valuable frame of reference for deepening the understanding of coloniality as a transcolonial phenomenon that globally unfolds across different postcolonial terrains. Theoretically, the article develops the idea of a body-knowledge-space configuration as a framework of analysis that simultaneously considers how structures and sentiments that emerged from colonialism frame contemporary realities within West and Non-West settings.